Evaluación del efecto de dos Compost en Combinación con un Fortificador (wayra) en el Cultivo de Papa Chaucha (solanum phureja), Yugsiloma, Juan Montalvo, Latacunga, 2017- 2018 - Tulpa Baltazaca, Gloria Jeaneth (2018)
The present research job carried out on the grounds of Mrs. Blanca Chancusig located in the Juan Montalvo parish, Cantón Latacunga, Cotopaxi Province at an altitude of 2,892 m.s.n.m. The objective was to evaluate the effect of two compost in combination with a fortifier (Wayra) in the cultivation of chaucha potato (Solanum phureja), We worked with a design of Complete Blocks at Chance (DBCA), with four repetitions and four treatments. For the variables, the variance analysis and the Tukey significance test were performed at 5% in the treatments where significance was found. In order to achieve the proposed objectives, the following variables were analyzed: days to emergence, plant height, incidence of pests, severity of diseases, number of root crops, weight of the root crops and yield per kg / ha The results obtained, the following was concluded: The treatment that presented the highest percentage of emergence was the control (where no type of fertilization was applied) with an average of 80.73%. Regarding height, the best treatment was the mixture of cow compost with the wayra fortifier, with an average of 17.43 cm. In the plots where no type of fertilization was applied (control plots) a higher incidence of pests and diseases was observed (with 39.29% and 49.30% of affectation, respectively). The plague that was detected was fleabane (Epitrix spp) and for diseases, it was identified (Phytophthora infestans). Similarly, the highest incidence of frost occurred in the control plots (73.94% affectation). The highest number of tubers / per plant was reached with the application of guinea pig compost with wayra fortifier (36.88 of tubers). In addition, the greatest weight was obtained with the application of cow compost with wayra fortifier with an average of 281.38 g / per treatment. In view of the results, it can be concluded that the wayra fortifier has no effect if applied alone; however, better values are appreciated in the different variables analyzed if it is combined with cow or guinea pig compost.